INVESTIGATING TYPE OF ISLAMIC INTEGRATION IN ENGLISH LANGUAGE TEACHING AT SMP YA BAKII 1 KESUGIHAN CILACAP - Abdul Basith; Ahmad Syafi’I; Yiyin Isgandi (STKIP Al Hikmah Surabaya, 2024)
This study was carried out to describe the types of Islamic integration taught in English Language Teaching in seventh grade Junior High School. In addition, the focus in this study is also to find out students’ and teachers’ responses related to English Language Teaching in seventh grade which is integrated with Islamic values. A qualitative descriptive research design was used in this study. The study involved one English teacher and six students of seventh grade. The type of integration in this study was proposed to Amin Abdullah. Based on the result of the study by interviewing and analyzing lesson plan, the researcher concluded that the type of integration carried out in English Language Learning was interconnected entities. In addition, based on the result of the students’ and teachers’ interview, students and teacher gave positive responses related to English learning which was integrated with Islamic values. English language teaching that integrated with Islamic values provided benefits and made students happy. In addition, students also got Islamic knowledge in learning and students feel not disturbed in understanding English lesson.